INVESTIGATION OF THE PHENOMENA OF FORGIVENESS: PSYCHOLOGICAL APPROACHES AND EMPIRICAL DATA - Гарькавець, Сергій Олексійович; Яковенко, Сергій Іванович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article presents the results of a theoretical and experimental study of grievances and forgiveness. It is established that forgiveness can be expressed as an act of nobility and mercy of a person who feels insulted. It was found that forgiveness depends on the age, sex and professional characteristics of the offended, from choosing a strategy of behaviour in confrontation with the one who offended him. On the basis of the developed two-dimensional model of the offense as personality traits, we identified five types of individual activity in a situation of resentment, which we called strategies of «rabbit», «fox», «sheep», «elephant» and «hippopotamus». Each of their strategies has its own algorithm of forgiveness and reconciliation with the offender. The strategy of «rabbit» implies a high level of anxiety, fear, modesty, depression and vulnerability, avoidance of the offender and everything related to the situation of resentment. The strategy of the «fox» envisages the consolidation and strengthening of a pleasant sense of superiority over the offender, forcing him to compensate for the offense inflicted and to smoothen his guilt. The strategy of the «sheep» is characterized by excessive intransigence of the offended, intractable, stubborn and hostile until the offender repents. The strategy of the «elephant» is aimed at the realization of revenge for the offense, and is characterized by the rigidity of the emotional sphere of the individual. The strategy of the «hippopotamus» provides a harsh and aggressive reaction to the offense, impossibility of forgiveness of the offender, since the manifestation of one’s own weakness is being considered. It is found out that women and men have differences in perception of resentment and readiness for its forgiveness, age characteristics affect the amplitude and intensity of the manifestations of offenses, and the sphere of professional activity leaves its imprint on the person’s attitude toward forgiveness and possible installations.